Pemanfaatan Teknologi Pendidikan bagi Pembelajaran Pendidikan Agama Islam di SMK Islam Terpadu Darul Abror Garut - Ega Rahmat Pauzi; Mahmud; Mohamad Erihadiana (STIT Fatahillah, 2023)
One of the global skills that needs to be developed in schools/madrasas is the use of technology. This study aims to analyze the use of educational technology for learning Islamic religious education (PAI) at the Integrated Islamic Vocational School Darul Abror Garut. Learning at the vocational high school level requires students to be ready to face technological developments in the industrial world. This study uses a qualitative approach. Data collection is done through interviews. The researcher then conducted a data analysis of the findings obtained. This study found that Darul Abror Integrated Islamic Vocational School has the resources and potential to support the application of educational technology. However, this advantage has not been utilized optimally by PAI teachers. This is due to the limitations of the teacher's information technology skills. The absence of cooperation between PAI teachers and other subject teachers who are competent in the technology field deepens the gap in the use of educational technology.